2015
DOI: 10.1177/1475725715592287
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Competencies in the Social Sciences

Abstract: The aim of the present study was to introduce a general theoretical model of scientific competencies in higher education and to adapt it to three social sciences, namely psychology, sociology, and political science, by providing evidence from expert interviews and program regulations. Within our general model, we distinguished and specified four building blocks of scientific competencies: input, operations, and output, as well as personal characteristics. We defined input as content students are exposed to in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 4 publications
0
16
0
1
Order By: Relevance
“…According to Klieme and Leutner (2006), competences are context-specific cognitive dispositions necessary to cope with situations and demands in specific domains. In their model of scientific competences in the social sciences, Dietrich et al (2015) conceptualize explanation as a cognitive process in which a causal relation is constructed. Following these two lines of reasoning, we define explanation competence as a context-specific cognitive disposition that enables a person to construct a causal model (see Kim, 1994) of an observable psychological phenomenon (like cognitive dissonance) by drawing on psychological theories.…”
Section: Explanation Competence and Learning From Worked Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Klieme and Leutner (2006), competences are context-specific cognitive dispositions necessary to cope with situations and demands in specific domains. In their model of scientific competences in the social sciences, Dietrich et al (2015) conceptualize explanation as a cognitive process in which a causal relation is constructed. Following these two lines of reasoning, we define explanation competence as a context-specific cognitive disposition that enables a person to construct a causal model (see Kim, 1994) of an observable psychological phenomenon (like cognitive dissonance) by drawing on psychological theories.…”
Section: Explanation Competence and Learning From Worked Examplesmentioning
confidence: 99%
“…Using psychological theories to explain psychological phenomena or, simply put, explaining a psychological phenomenon, is not only a part of the definition of psychology as a science (e.g., Gerrig & Zimbardo, 2010), but also a component of scientific competence in psychology (Dietrich et al., 2015). In psychology teaching, learning the content of scientific theories is emphasized, especially for novice students (see Birke, Rosman & Mayer, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Acquiring scientific argumentation competence is a major goal of higher education study programs (Dietrich et al, 2015). In general, argumentation refers to the use of arguments for the sake of supporting a certain claim with a reason to persuade others of the claim's validity (Lumer, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the former example in Type 2 form is "Studies found that extrovert people show a statistically higher amount of social contacts with strangers than introvert people, thus extroverts are more likely to have social contacts with strangers." In the context of a competencybased approach, the use of scientific evidence to support claims can be described as a domain-specific disposition (cf., Klieme and Leutner, 2006;Dietrich et al, 2015) that is acquired within a study program. Thus, the correct use of argumentation is a competence which is hereafter referred to as argumentation competence.…”
Section: Introductionmentioning
confidence: 99%
“…The enculturation in the domain therefore leads to epistemological beliefs that are not favorable for the development of sophisticated argumentation skills (cf., Kuhn, 2001). Taken for granted that scientific argumentation skills are a centerpiece of scientific competencies (cf., Dietrich et al, 2015;Fischer et al, 2016), it seems therefore necessary to foster psychology students' evaluatist epistemological beliefs systematically. This article presents the evaluation of a computer-based version of the epistemological belief instruction by Rosman, Mayer, Peter and Krampen (2016) to foster evaluativist epistemological beliefs in psychology students.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%